2021
DOI: 10.3390/ijms23010362
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function Relationships in the Human P-Glycoprotein (ABCB1): Insights from Molecular Dynamics Simulations

Abstract: P-glycoprotein (P-gp) is a transmembrane protein belonging to the ATP binding cassette superfamily of transporters, and it is a xenobiotic efflux pump that limits intracellular drug accumulation by pumping compounds out of cells. P-gp contributes to a reduction in toxicity, and has broad substrate specificity. It is involved in the failure of many cancer and antiviral chemotherapies due to the phenomenon of multidrug resistance (MDR), in which the membrane transporter removes chemotherapeutic drugs from target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 60 publications
2
24
0
Order By: Relevance
“…Support for a size-dependent behavior may be found in the literature, where stipiamide monomers show a low efficiency at small concentrations and a cooperative behavior in the inhibition of IAAP binding to P–gp, while covalent dimers of stipiamide are more efficient and show a simple dependence with concentration [ 101 ] or a more efficient inhibition of P–gp transport activity by bisbenzylisoquinoline alkaloids [ 102 ]. Further evidence for the binding of several molecules in P–gp’s binding pocket has also been obtained from docking studies (e.g., [ 9 , 29 , 79 , 103 , 104 , 105 , 106 , 107 , 108 ]).…”
Section: Discussionmentioning
confidence: 95%
“…Support for a size-dependent behavior may be found in the literature, where stipiamide monomers show a low efficiency at small concentrations and a cooperative behavior in the inhibition of IAAP binding to P–gp, while covalent dimers of stipiamide are more efficient and show a simple dependence with concentration [ 101 ] or a more efficient inhibition of P–gp transport activity by bisbenzylisoquinoline alkaloids [ 102 ]. Further evidence for the binding of several molecules in P–gp’s binding pocket has also been obtained from docking studies (e.g., [ 9 , 29 , 79 , 103 , 104 , 105 , 106 , 107 , 108 ]).…”
Section: Discussionmentioning
confidence: 95%
“…The P-gp transporter has been shown to efflux a diverse range of molecules with varying chemical structures (cyclic, polar, nonpolar, linear, aromatic, linear-lipophilic) and molecular weights (250-4000 Da) (Table 1). Among the first P-gp competitive inhibitors discovered were cyclosporine-A and verapamil [77,78]. In a recent high-throughput screen of 10,804 compounds, Lee et al discovered 90 substrates, 55 of which were novel.…”
Section: Substrates Of P-gp and Its Drug Interactionmentioning
confidence: 99%
“…These efflux transporters are essential for the prevention and treatment of adverse reactions caused by opioid abuse and overdose. ABCB1-coded P-glycoprotein (P-gp) is an efflux transporter that limits intracellular drug accumulation by pumping compounds out of cells [17]. A study in mice showed that P-gp is one of the main components of the blood-cerebrospinal fluid (CSF) barrier.…”
Section: Abcb1mentioning
confidence: 99%